A cross-sectional study of female sexual dysfunction among Turkish pregnant and nonpregnant women: correlation with hormone profile - Sarıibrahim Astepe, Bahar; Köleli, İşıl (The European Research Journal, 2019)
Objectives: To determine the prevalence of female sexual dysfunction (FSD) and its correlation with the androgenic hormones among pregnant and nonpregnant Turkish women.Methods: This was a cross-sectional study of 251 women, including 137 healthy pregnant and 114 healthy nonpregnant Turkish women. Assessment of female sexual function index (FSFI), sociodemographic characteristics, serum androgen levels, including the total testosterone, dehydroepiandrosterone sulfate (DHEAS), 1-4 delta androstenedione.Results: There was a 65.7 % incidence of FSD in all of the participants, with an incidence of 58.8% in the pregnant and 41.2% in the nonpregnant women. There was no significant difference in the FSFI total scores between the pregnant and nonpregnant women (p > 0.05). Moreover, the androgen levels were not different between the women with sexual dysfunction and those without. The Spearman correlation test results were significant between the total testosterone level and the FSFI arousal domain (r=0.167, p < 0.05), FSFI lubrication domain (r=0.264, p < 0.01), and FSFI total score (r=0.212, p < 0.01)., as well as between the androstenedione level and FSFI lubrication domain (r=0.211, p < 0.01), FSFI orgasm domain (r=0.156, p < 0.05), and FSFI total score (r=0.174, p < 0.05). In the logistic regression analysis for sexual dysfunction, an increase in the DHEAS level increased the sexual dysfunction by 0.996-fold. Women with one pregnancy had 3.312-fold greater sexual dysfunction than those with no pregnancies. Moreover, the women with more than eight years of education had 0.358 times more sexual dysfunction than those with eight years of education and less. Conclusion: The FSFI total scores were not significantly different between the pregnant and nonpregnant women. However, there were significant correlations between the total testosterone and androstenedione levels and the FSFI total scores. Any increases in the DHEAS level and educational level in women decrease the chance of developing sexual dysfunction.